2013
DOI: 10.4236/psych.2013.43029
|View full text |Cite
|
Sign up to set email alerts
|

Conscripted without Induction Order: Wives of Former Combat Veterans with PTSD Speak

Abstract: This study examines the lives of wives who are living with former combat soldiers with chronic PTSD, from the subjective perspective of the wives themselves. Structured interviews with 20 wives indicated the following main results: 1) About 2/3 of the wives reported that, for a long time, they did not know what the problem with their husband was and had no idea that it was connected to his military experience. 2) All of the wives described many negative effects of their husband's situation on daily family func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…"Commitment" to the relationship was a key theme in this study, reflecting a "motivating quality which helps sustain coping effort" (Lazarus & Folkman, 1984, p. 63). "Commitment" was reinforced by a strong moral responsibility, a finding made in other studies of partners of veterans (Dekel et al, 2005;Kimhi, 2013;Lyons, 2001), as well as the acceptance of the dominant paradigm of mental illness. This paradigm views PTSD in veterans as an illness attributable to military service.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…"Commitment" to the relationship was a key theme in this study, reflecting a "motivating quality which helps sustain coping effort" (Lazarus & Folkman, 1984, p. 63). "Commitment" was reinforced by a strong moral responsibility, a finding made in other studies of partners of veterans (Dekel et al, 2005;Kimhi, 2013;Lyons, 2001), as well as the acceptance of the dominant paradigm of mental illness. This paradigm views PTSD in veterans as an illness attributable to military service.…”
Section: Discussionmentioning
confidence: 72%
“…There is, however, very limited literature that specifically examines the needs of partners caring for a veteran with PTSD. Even the limited numbers of qualitative studies undertaken with partners (Dekel, Goldblatt, Keidar, Solomon, & Polliack, 2005;Kimhi, 2013;Lyons, 2001;Verbosky & Ryan, 1988) are mainly based in clinical settings providing treatment for veterans and address need in terms of recommendations for counseling and therapy. Lack of research into needs of partners as perceived by the partners themselves could result in suggestions for interventions or services that fail to meet need.…”
mentioning
confidence: 99%
“…Many service members with post‐traumatic stress disorder (PTSD) and TBI may isolate themselves from family members and friends, which likely affects family experiences in negative ways. Other research has examined the impact of psychological trauma on the leisure of military wives (Kimhi & Doron, ), wherein wives indicated they participated in leisure activities with friends and other family members, as opposed to their spouses, because the psychological trauma kept their husbands from being able to leave their homes. The decrease in family leisure may be due to activities and experiences that trigger symptoms like anger, aggression, and hyperarousal; however, the impact of psychological traumas on military family leisure experiences has not been extensively studied.…”
Section: Creation Of Military Family Leisure Experiencesmentioning
confidence: 99%
“…Those studies that have examined women in the context of armed conflict have been confined to a number of specific and focused topics, namely, sexual harassment of women soldiers during their military service (Castro, Kintzle, Schuyler, Lucas, & Warner, ; Maguen et al, ; Mattocks et al, ; Wolfe et al, ); war widows and orphans (Kamya, ; Kumar, ); secondary traumatization of women spouses of combatants (Dekel & Monson, ; Kimhi & Doron, ); the effects of being in proximity to a war zone (Duramy, ; Hynes, ) or to a civil war (McKay, ); sexual crimes against civilian women in conflict zones (Cohen, ; Denov, ); and the comparative effect of childhood traumas on men and women soldiers (Kelley et al, ; Mota et al, ). An exception is the recent study of Jacobson, Donoho, Crum‐Cianflone, and Maguen, () examining gender differences among combatants who had been deployed in Iraq and Afghanistan; they found that women and men combatants did not have a significantly different risk for developing PTSD.…”
Section: Women Combatants and Traumamentioning
confidence: 99%